2018
DOI: 10.1016/j.neuroimage.2018.01.062
|View full text |Cite
|
Sign up to set email alerts
|

Direct electrophysiological evidence for the maintenance of retrieval orientations and the role of cognitive control

Abstract: Retrieval orientations are memory states that bias retrieval towards specific memory contents. Many neuroimaging studies have examined the influence of retrieval orientations on stimulus processing, but very little direct evidence exists regarding the ongoing maintenance of orientations themselves. Participants completed two memory tasks with different retrieval goals. ERPs were time-locked to a pre-stimulus fixation asterisk and contrasted according to retrieval goals. Pre-stimulus ERPs elicited during the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 63 publications
(109 reference statements)
3
19
1
Order By: Relevance
“…Supporting a maintenance interpretation, the stay trial ERPs observed here closely resemble those obtained in a recent experiment which maintained retrieval goals across multiple successive trials (Herron, 2018). Frontal pre-retrieval ERPs were more positive-going when participants retrieved visualisation-based information than when they retrieved encoding operations, and this was interpreted as a direct correlate of retrieval orientation maintenance across trials.…”
Section: Discussionsupporting
confidence: 83%
“…Supporting a maintenance interpretation, the stay trial ERPs observed here closely resemble those obtained in a recent experiment which maintained retrieval goals across multiple successive trials (Herron, 2018). Frontal pre-retrieval ERPs were more positive-going when participants retrieved visualisation-based information than when they retrieved encoding operations, and this was interpreted as a direct correlate of retrieval orientation maintenance across trials.…”
Section: Discussionsupporting
confidence: 83%
“…A second possibility is that episodic memory states may facilitate the accuracy of judgments by influencing processes that operate on the products of retrieval, such as post-retrieval monitoring processes. Some recent data from our lab ( Herron, 2018 ) indicates that there is in fact a trade-off between the maintenance of retrieval orientations and post-retrieval monitoring. In this study, participants were required to complete two blocked memory tasks with different retrieval goals.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of the effect on stay trials in the present study is consistent with the notion that it indexes task configuration processes that are involved in the initiation of orientation as opposed to its ongoing maintenance across items. There is some evidence that processes involved in the initiation and maintenance of retrieval orientations have dissociable ERP correlates ( Herron and Wilding, 2006b , Herron et al., 2016 ), with those associated with maintenance predominantly being evident when retrieval requirements are blocked as opposed to alternating ( Herron and Wilding, 2006b , Herron, 2018 , Johnson and Rugg, 2006 , Werkle-Bergner et al., 2005 , Wilding and Nobre, 2001 ; but see; Herron et al., 2016 ). Second, the preparatory ERP effect observed here was broadly distributed across frontal sites.…”
Section: Discussionmentioning
confidence: 99%
“…This version also led to an increase in the production of internal details in memory and imagination tasks, without having any effect on the details generated in a picture description task as in the standard ESI. The authors argue that the ESI effects in both versions come from the retrieval orientation bias (Rugg and Wilding, 2000; Morcom and Rugg, 2012; Herron, 2018). Participants would focus their controlled retrieval attempts more on specific elements (setting, objects, people, and actions) during the ESI (Schacter and Madore, 2016).…”
Section: Introductionmentioning
confidence: 99%